Use of erythromycin and metoclopramide in hospitalized dogs: a multicenter historical cohort study - Teo, Ee Fung; Sharp, Claire R.; Boyd, Corrin J.; Chee, Weiqin (Frontiers in Veterinary Science, 2025)
IntroductionProkinetics are used to treat gastrointestinal (GI) dysmotility in critically ill dogs but there have been no published studies characterizing their use. The objective of this multi-institutional retrospective cohort study was to describe the use of the prokinetics erythromycin and metoclopramide in dogs hospitalized in two institutions. We hypothesized that there would be change over time and differences between institutions in the use of erythromycin and metoclopramide.MethodsDogs for inclusion were identified by fee code searches for injectable erythromycin and metoclopramide in the electronic medical record systems of The Animal Hospital at Murdoch University and Western Australian Veterinary Emergency and Specialty Hospital for the years 2018 and 2023. 75 cases from each hospital in each year were selected for inclusion from the search results using a formal randomization procedure to yield a total case number of 300. Data collected for each dog included signalment, diagnosis, reason(s) for starting prokinetics, the injectable prokinetic(s) used, frequency, and doses. Chi square or Fisher’s exact tests were used as appropriate to compare the proportions of dogs receiving metoclopramide alone, erythromycin alone, or both prokinetics in 2018 and 2023, the proportions of dogs receiving metoclopramide or erythromycin as sole prokinetics between the two institutions, and the proportions of dogs receiving a single prokinetic versus dual prokinetics between the two institutions.ResultsPrimary GI diseases accounted for the majority of the diagnoses. The most common reasons for starting a prokinetic were vomiting, an imaging diagnosis of ileus, prophylaxis following abdominal surgery, and regurgitation. Metoclopramide was administered as a sole prokinetic in the majority of dogs, fewer cases received erythromycin alone, or both prokinetics. Use of metoclopramide alone decreased from 2018 to 2023, with more dogs receiving erythromycin alone or both prokinetics in 2023. There were also significant differences in prokinetic use between institutions.DiscussionProspective studies to investigate the effectiveness and safety of metoclopramide and erythromycin as prokinetics in dogs are warranted.